Melon13-lipoxygenase CmLOX18 may be involved in C6 volatiles biosynthesis in fruit - Chong Zhang (Nature Portfolio, 2017)
Abstract To better understand the function role of the melon CmLOX18 gene in the biosynthesis of C6 volatiles during fruit ripening, we biochemically characterized CmLOX18 and identified its subcellular localization in transgenic tomato plants. Heterologous expression in yeast cells showed that the molecular weight of the CmLOX18 protein was identical to that predicted, and that this enzyme possesseed lipoxygenase activity. Linoleic acid was demonstrated to be the preferred substrate for the purified recombinant CmLOX18 protein, which exhibited optimal catalytic activity at pH 4.5 and 30 °C. Chromatogram analysis of the reaction product indicated that the CmLOX18 protein exhibited positional specificity, as evidenced by its release of only a C-13 oxidized product. Subcellular localization analysis by transient expression in Arabidopsis protoplasts showed that CmLOX18 was localized to non-chloroplast organelles. When the CmLOX18 gene was transgenically expressed in tomato via Agrobacterium tumefaciens-mediated transformation, it was shown to enhance expression levels of the tomato hydroperoxide lyase gene LeHPL, whereas the expression levels of six TomLox genes were little changed. Furthermore, transgenic tomato fruits exhibited increases in the content of the C6 volatiles, namely hexanal, (Z)-3-hexanal, and (Z)-3-hexen-1-ol, indicating that CmLOX18 probably plays an important role in the synthesis of C6 compounds in fruits.